(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2020)
This paper explores the relation between perception and recognizability in the work of Honneth, Rancière and Butler. Recognizability is the term employed here to indicate the perceptual process that necessarily occurs prior to a normative or ethical act of recognition and that provides the conditions that make recognition possible. The notion of recognizability points to the fact that perception is not merely a disinterested surveying of the perceptual field but indicates that it is already evaluative in the sense that others are immediately distinguishable from other objects. When recognizability fails, it is not because the other has not been seen in a literal sense but instead that she has been intentionally ignored or invisibilized. The suggestion made here is that despite their different approaches, a comparison and dialogue between these three thinkers highlights the importance of this constellation of issues for critical theory.